The Poetics of Jora Fozil's Stories - Abdullayeva Farangiz Azim qizi; Qodirova Nasima Saidburkhonovna (Indonesian Journal of Innovation Studies, 2022)
The article describes the peculiarities of the prose of Bukhara writer Jora Fozil. A number of stories have been analyzed in terms of language, style, theme, and structure. The author's stories are about the skill of creating a landscape.